Method for selectively extracting scandium from red mud through ferric sulfate roasting and water leaching

Through the ferric sulfate water immersion method, scandium is efficient and selectively extracted from red mud, which solves the problems of large acid use, high acidity of water-immersion residues and ammonia emissions in the prior art, and achieves environmentally friendly and low-cost scandium extraction effect.

CN119736489APending Publication Date: 2025-04-01INST OF GEOCHEMISTRY CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411736313.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

In the existing scandium separation and extraction technology in red mud, environmental problems such as large acid use, high acidity of water-immersed residues, and harmful ammonia gas produced during roasting.

Method used

Scandium was selectively extracted from red mud by using the ferric sulfate water immersion method. The method includes grinding the red mud with iron sulfate, performing calcination and water-impregnation reactions, and obtaining a scandium-containing leaching liquid by solid-liquid separation.

Benefits of technology

The extraction of highly selective scandium is achieved, and the use of high concentrations of acid and ammonia emissions are avoided. The process is simple, the cost is low and the environment is friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736489A_ABST
    Figure CN119736489A_ABST
Patent Text Reader

Abstract

The invention discloses a method for selectively extracting scandium from red mud through ferric sulfate roasting and water leaching, and belongs to the technical field of recovery of valuable elements in the red mud. The method comprises the following steps that red mud and ferric sulfate are mixed and ground to obtain a mixture, the mixture is roasted, water is added into the obtained roasted clinker for a water leaching reaction, and the scandium-containing leachate is obtained. According to the method, the purpose of selectively recovering scandium resources from the red mud is achieved through the method that ferric sulfate roasting is combined with water leaching, and the scandium leaching rate can reach 80% or above. The method is low in cost, high in recovery rate, good in selectivity, environment-friendly and simple in process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of recovering valuable elements in red mud, and in particular relates to a method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching. Background Art

[0002] The rare earth element scandium is widely used in metallurgy, military, materials and chemical engineering due to its excellent physical and chemical properties such as magnetism, light, and electricity. However, due to the relatively small number of independent scandium deposits in nature, the price of scandium is significantly higher than that of other rare earth elements. Red mud is an industrial solid waste produced in the process of producing alumina from bauxite. It contains valuable elements such as iron, aluminum, titanium, and rare earths. The content of rare earths is generally twice that of bauxite, and it has recycling value. Among the existing technologies for separating and extracting scandium from red mud, most of them use concentrated sulfuric acid or ammonium sulfate for sulfidation roasting to react with scandium-containing minerals to form metal sulfates such as scandium, iron, aluminum, and calcium. The roasting temperature is controlled by using the difference in the thermal decomposition temperature of metal sulfates, so that when sulfates such as iron and aluminum are decomposed into oxides, scandium sulfate remains undecomposed. Finally, water leaching is performed to achieve selective dissolution of soluble scandium sulfate.

[0003] There are now a variety of methods for extracting scandium using concentrated sulfuric acid or ammonium sulfate sulfidation roasting methods. For example, the Chinese patent technology (publication number CN106086436A) uses concentrated sulfuric acid to mix with red mud, low-temperature sulfate sulfidation and then medium-temperature roasting, and finally water leaching to obtain a scandium-rich leachate. Similarly, concentrated sulfuric acid is also used to mix with laterite nickel ore for roasting and extracting scandium (publication number CN114480887A), and the resulting water-leached scandium-containing solution is precipitated with oxalic acid and calcined to obtain scandium oxide. In the above-mentioned related art inventions, concentrated sulfuric acid is used for sulfidation roasting, the acid usage is large, and the water leaching residue is highly acidic. In order to avoid the above-mentioned shortcomings, less or no concentrated sulfuric acid is used. The prior art (publication number CN110331289A) uses ammonium sulfate to roast red mud in two stages, and then the roasted product is multi-stage water-leached and then adsorbed and recovered by an adsorbent to recover the scandium in the leachate, thereby achieving the purpose of recovering scandium from red mud. Another prior art (publication number CN112795784A) mixes red mud, ammonium sulfate salt and sulfuric acid in a water vapor atmosphere, and then obtains a scandium-containing leachate through roasting and water leaching. In the above-mentioned related technical inventions, ammonium sulfate is used to replace or partially replace concentrated sulfuric acid for sulfidation roasting. However, the ammonium sulfate roasting process produces ammonia, which is not environmentally friendly. In summary, the existing invention technology of sulfidation roasting to recover scandium can achieve certain effects, but there are still defects in application, such as large amount of acid used, high acidity of water leaching residue, and emission of ammonia tail gas. Summary of the invention

[0004] In order to solve the above technical defects, the present invention proposes a method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching. The method has simple process, low cost, high extraction rate, environmental friendliness, and practical application value.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching comprises the following steps: mixing red mud and ferric sulfate and grinding them to obtain a mixture, roasting the mixture, adding water to the obtained roasted clinker to carry out a water leaching reaction, and separating the solid from the liquid to obtain a leaching solution containing scandium.

[0007] Ferric sulfate is a low-cost reagent that is relatively friendly to equipment and the environment. By adding ferric sulfate to replace concentrated sulfuric acid and ammonium sulfate to react with red mud during the roasting process, metal sulfates such as scandium, iron, and aluminum are generated. Subsequently, sulfates such as iron and aluminum are decomposed into corresponding oxides, while scandium sulfate remains undecomposed due to its high thermal decomposition temperature, and selective dissolution from red mud is achieved under water immersion treatment. In addition, the use of ferric sulfate for sulfidation roasting can not only achieve highly selective dissolution of the scandium element, but also avoid the use of high-concentration acid and the emission of tail gases such as ammonia.

[0008] Furthermore, the mass ratio of the red mud to ferric sulfate is 1:(1.0-1.2).

[0009] Furthermore, the grinding is performed until the obtained powder passes through a 200-mesh sieve.

[0010] Furthermore, the calcination temperature is 700° C. and the calcination time is 15 minutes.

[0011] Furthermore, the ratio of the roasted clinker to water is 1 g: 10 mL.

[0012] Furthermore, the water immersion reaction is carried out at a temperature of 25-80° C. and for a time of 30-180 minutes.

[0013] Compared with the prior art, the present invention has the following advantages and technical effects:

[0014] Ferric sulfate is a low-cost and environmentally friendly reagent that can avoid the use of high-concentration acid and the emission of gases such as ammonia during the roasting process. The present invention uses ferric sulfate for sulfidation roasting to achieve highly selective dissolution of scandium in red mud. Compared with existing technical solutions, it has the characteristics of being relatively environmentally friendly and easy to operate.

[0015] The leaching rate of scandium in the scandium-containing leaching solution obtained by the method of the invention can reach up to more than 80%. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0017] Figure 1 It is an operation flow chart of the present invention. DETAILED DESCRIPTION

[0018] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0019] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0020] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0021] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0022] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0023] A method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching, comprising the following steps:

[0024] (1) Mixing: Weigh the corresponding mass of red mud and iron sulfate in a set ratio, pour them into a mortar, grind and mix them, and then sieve the mixture to ensure its uniformity;

[0025] (2) Calcination: Pour the mixture of red mud and ferric sulfate obtained in step (1) into a quartz boat and place it in a high-temperature box furnace, and perform calcination at a set temperature and time to obtain calcined clinker;

[0026] (3) Water immersion: Mix the roasted clinker obtained in step (2) and pure water in a conical flask and place it in a constant temperature water bath oscillator for reaction;

[0027] (4) Filtration: After the reaction in step (3) is completed, centrifugal filtration is performed to separate the solid and liquid to obtain a scandium-containing leaching solution.

[0028] In the following embodiments of the present invention, the mass ratio of red mud to ferric sulfate in step (1) is 1:(1.0-1.2). Exemplarily, in the following preferred embodiments of the present invention, the mass ratio of red mud to ferric sulfate is 1:1.0, 1:1.2 or any range between the aforementioned ratios.

[0029] In the following examples of the present invention, the size of the sieve used in the sieving process in step (1) is 200 mesh.

[0030] In the following examples of the present invention, the calcination temperature in step (2) is 700° C. and the calcination time is 15 minutes.

[0031] In the following examples of the present invention, the ratio of the roasted clinker to water in step (3) is 1 g: 10 mL.

[0032] In the following embodiments of the present invention, the temperature of the water leaching reaction in step (3) is 25-80°C. This temperature range is the general range that water temperature can reach. Within this range, the leaching effect of scandium is similar, and the leaching rate of scandium will be lower below room temperature. Exemplarily, in the following preferred embodiments of the present invention, the temperature of the water leaching reaction is 25°C, 40°C, 60°C, 80°C or any value between the aforementioned range values. The time of the water leaching reaction is 30-180 minutes, and the leaching effect of scandium for 30 minutes and 180 minutes is similar. If the leaching time is further extended, the leaching effect will not deteriorate, nor will it increase significantly, and energy consumption will increase. Exemplarily, in the following preferred embodiments of the present invention, the time of the water leaching reaction is 30 minutes, 60 minutes, 180 minutes or any value between the aforementioned range values.

[0033] In the following examples of the present invention, the leaching rate of scandium in the scandium-containing leaching solution obtained by the method of the present invention in step (4) can reach more than 71%, while the leaching rate of iron is less than 13%, and the leaching rate of aluminum is less than 21%. The low leaching rates of iron and aluminum indicate that the method of the present invention has high selectivity for leaching scandium.

[0034] The "normal temperature" mentioned in the present invention refers to 20-30°C unless otherwise specified.

[0035] The raw materials used in the present invention are all purchased from the market.

[0036] The “parts” described in the present invention are all measured by “parts by mass” unless otherwise specified.

[0037] The technical solution of the present invention is further illustrated by the following embodiments.

[0038] Figure 1 It is an operation flow chart of the present invention.

[0039] In the following embodiments of the present invention, the red mud used was collected from the red mud yard of an aluminum plant in Guizhou Province, and the contents of the main elements (in terms of oxides) were as follows: Al2O3 was 13.22%, SiO2 was 18.33%, Fe2O3 was 11.67%, TiO2 was 3.90%, CaO was 10.32%, Na2O was 4.58%, and Sc was 71.3 μg / g (i.e., 0.0713%).

[0040] Example 1

[0041] Weigh 10 parts of red mud and 10 parts of ferric sulfate (i.e., the mass ratio is 1.0:1.0), grind and mix in a mortar, and pass through a 200-mesh sieve. Put the sieved mixture into a quartz boat and place it in a high-temperature box furnace. Set the roasting temperature to 700°C and the insulation time to 15 minutes. After the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker. Mix the roasted clinker and water in a conical flask with a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 25°C to react for 30 minutes. After the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0042] According to the test, the pH value of the scandium-containing leaching solution is 2.65, the leaching rate of scandium is 77.1%, the leaching rate of iron is 6.8%, and the leaching rate of aluminum is 11.3%.

[0043] Example 2

[0044] Weigh 10 parts of red mud and 10 parts of ferric sulfate (i.e., the mass ratio is 1.0:1.0), grind and mix in a mortar and pass through a 200-mesh sieve, put the sieved mixture into a quartz boat and place it in a high-temperature box furnace, set the roasting temperature to 700°C, and keep it warm for 15 minutes; after the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker, mix the roasted clinker with water in a conical flask at a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 40°C to react for 30 minutes, and perform solid-liquid separation after the reaction to obtain a scandium-containing leaching solution.

[0045] According to the test, the pH value of the scandium-containing leaching solution is 2.38, the leaching rate of scandium is 77.4%, the leaching rate of iron is 5.2%, and the leaching rate of aluminum is 13.0%.

[0046] Example 3

[0047] Weigh 10 parts of red mud and 10 parts of ferric sulfate (i.e., the mass ratio is 1.0:1.0), grind and mix in a mortar and pass through a 200-mesh sieve, put the sieved mixture into a quartz boat and place it in a high-temperature box furnace, set the roasting temperature to 700°C, and keep it warm for 15 minutes; after the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker, mix the roasted clinker and water in a conical flask at a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 80°C to react for 30 minutes, and after the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0048] According to the test, the pH value of the scandium-containing leaching solution is 1.90, the leaching rate of scandium is 74.3%, the leaching rate of iron is 1.6%, and the leaching rate of aluminum is 13.7%.

[0049] Example 4

[0050] Weigh 10 parts of red mud and 10 parts of ferric sulfate (i.e., the mass ratio is 1.0:1.0), grind and mix in a mortar, and pass through a 200-mesh sieve. Put the sieved mixture into a quartz boat and place it in a high-temperature box furnace. Set the roasting temperature to 700°C and the insulation time to 15 minutes. After the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker. Mix the roasted clinker and water in a conical flask with a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 25°C to react for 60 minutes. After the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0051] According to the test, the pH value of the scandium-containing leaching solution is 2.60, the leaching rate of scandium is 78.0%, the leaching rate of iron is 6.2%, and the leaching rate of aluminum is 12.6%.

[0052] Example 5

[0053] Weigh 10 parts of red mud and 10 parts of ferric sulfate (i.e., the mass ratio is 1.0:1.0), grind and mix in a mortar and pass through a 200-mesh sieve, put the sieved mixture into a quartz boat and place it in a high-temperature box furnace, set the roasting temperature to 700°C, and keep warm for 15 minutes; after the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker, mix the roasted clinker and water in a conical flask at a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 25°C to react for 180 minutes, and perform solid-liquid separation after the reaction to obtain a scandium-containing leaching solution.

[0054] According to the test, the pH value of the scandium-containing leaching solution is 2.52, the leaching rate of scandium is 78.8%, the leaching rate of iron is 5.1%, and the leaching rate of aluminum is 13.1%.

[0055] Example 6

[0056] Weigh 10 parts of red mud and 10 parts of ferric sulfate (i.e., the mass ratio is 1.0:1.0), grind and mix in a mortar and pass through a 200-mesh sieve, put the sieved mixture into a quartz boat and place it in a high-temperature box furnace, set the roasting temperature to 700°C, and keep it warm for 15 minutes; after the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker, mix the roasted clinker and water in a conical flask at a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 60°C to react for 60 minutes, and after the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0057] According to the test, the pH value of the scandium-containing leaching solution is 2.11, the leaching rate of scandium is 74.8%, the leaching rate of iron is 2.1%, and the leaching rate of aluminum is 13.6%.

[0058] Example 7

[0059] Weigh 10 parts of red mud and 10 parts of ferric sulfate (i.e., the mass ratio is 1.0:1.0), grind and mix in a mortar, and pass through a 200-mesh sieve. Put the sieved mixture into a quartz boat and place it in a high-temperature box furnace. Set the roasting temperature to 700°C and the insulation time to 15 minutes. After the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker. Mix the roasted clinker and water in a conical flask with a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 60°C to react for 180 minutes. After the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0060] According to the test, the pH value of the scandium-containing leaching solution is 2.22, the leaching rate of scandium is 71.8%, the leaching rate of iron is 1.3%, and the leaching rate of aluminum is 14.3%.

[0061] Example 8

[0062] Weigh 10 parts of red mud and 12 parts of ferric sulfate (i.e., the mass ratio is 1:1.2) in a mortar, grind and mix them, and pass them through a 200-mesh sieve. Put the sieved mixture into a quartz boat and place it in a high-temperature box furnace. Set the roasting temperature to 700°C and the insulation time to 15 minutes. After the roasting process is completed, cool it to room temperature and take it out to obtain the roasted clinker. Mix the roasted clinker and water in a conical flask with a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 25°C to react for 30 minutes. After the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0063] The pH of the scandium-containing leaching solution was 2.60, the leaching rate of scandium was 75.6%, the leaching rate of iron was 12.7%, and the leaching rate of aluminum was 16.9%.

[0064] Example 9

[0065] Weigh 10 parts of red mud and 12 parts of ferric sulfate (i.e., the mass ratio is 1:1.2) in a mortar, grind and mix them, and pass them through a 200-mesh sieve. Put the sieved mixture into a quartz boat and place it in a high-temperature box furnace. Set the roasting temperature to 700°C and the insulation time to 15 minutes. After the roasting process is completed, cool it to room temperature and take it out to obtain the roasted clinker. Mix the roasted clinker and water in a conical flask with a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 40°C to react for 30 minutes. After the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0066] According to the test, the pH value of the scandium-containing leaching solution is 2.40, the leaching rate of scandium is 81.0%, the leaching rate of iron is 11.5%, and the leaching rate of aluminum is 19.1%.

[0067] Example 10

[0068] Weigh 10 parts of red mud and 12 parts of ferric sulfate (i.e., the mass ratio is 1:1.2), grind and mix in a mortar and pass through a 200-mesh sieve, put the sieved mixture into a quartz boat and place it in a high-temperature box furnace, set the roasting temperature to 700°C, and keep it warm for 15 minutes; after the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker, mix the roasted clinker and water in a conical flask at a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 80°C to react for 30 minutes, and after the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0069] According to the test, the pH value of the scandium-containing leaching solution is 1.90, the leaching rate of scandium is 80.0%, the leaching rate of iron is 3.9%, and the leaching rate of aluminum is 21%.

[0070] Embodiment 11

[0071] Weigh 10 parts of red mud and 12 parts of ferric sulfate (i.e., the mass ratio is 1:1.2), grind and mix in a mortar and pass through a 200-mesh sieve, put the sieved mixture into a quartz boat and place it in a high-temperature box furnace, set the roasting temperature to 700°C, and keep it warm for 15 minutes; after the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker, mix the roasted clinker and water in a conical flask at a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 25°C to react for 60 minutes, and after the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0072] According to the test, the pH value of the scandium-containing leaching solution is 2.66, the leaching rate of scandium is 77.2%, the leaching rate of iron is 11.1%, and the leaching rate of aluminum is 17.5%.

[0073] Example 12

[0074] Weigh 10 parts of red mud and 12 parts of ferric sulfate (i.e., the mass ratio is 1:1.2) in a mortar, grind and mix them, and pass them through a 200-mesh sieve. Put the sieved mixture into a quartz boat and place it in a high-temperature box furnace. Set the roasting temperature to 700°C and the insulation time to 15 minutes. After the roasting process is completed, cool it to room temperature and take it out to obtain the roasted clinker. Mix the roasted clinker and water in a conical flask with a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 25°C to react for 180 minutes. After the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0075] According to the test, the pH value of the scandium-containing leaching solution is 2.54, the leaching rate of scandium is 80.2%, the leaching rate of iron is 10.2%, and the leaching rate of aluminum is 19%.

[0076] Comparative Example 1

[0077] Weigh 10 parts of red mud, grind and mix in a mortar, and pass through a 200-mesh sieve. Put the sieved mixture into a quartz boat and place it in a high-temperature box furnace. Set the roasting temperature to 700°C and the insulation time to 60 minutes. After the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker. Mix the roasted clinker and water in a conical flask at a solid-liquid ratio of 1g:10mL and place it in a constant temperature water bath oscillator at 25°C to react for 30 minutes. After the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0078] The leaching rate of scandium was found to be 0%.

[0079] Comparative Example 2

[0080] Weigh 10 parts of red mud and 10 parts of ferric sulfate (i.e., the mass ratio is 1.0:1.0) to obtain a mixture, mix the mixture with water at a solid-liquid ratio of 1 g:10 mL in a conical flask and place it in a constant temperature water bath oscillator at 25°C to react for 30 minutes. After the reaction is completed, solid-liquid separation is performed to obtain a scandium-containing leaching solution.

[0081] According to the test, the leaching rate of scandium is 14%.

[0082] By comparing the examples and comparative examples, it can be seen that the extraction of scandium by directly roasting red mud and then leaching it in water, or by directly leaching red mud and ferric sulfate without roasting them, is not ideal.

[0083] Comparative Example 3

[0084] Weigh 10 parts of red mud and 10 parts of ferrous sulfate (i.e., the mass ratio is 1.0:1.0), grind and mix in a mortar and pass through a 200-mesh sieve, put the sieved mixture into a quartz boat and place it in a high-temperature box furnace, set the roasting temperature to 700°C, and keep it warm for 60 minutes; after the roasting process is completed, cool to room temperature and take out to obtain the roasted clinker, mix the roasted clinker and water in a conical flask at a solid-liquid ratio of 1g:5mL and place it in a constant temperature water bath oscillator at 25°C to react for 60 minutes, and after the reaction is completed, perform solid-liquid separation to obtain a scandium-containing leaching solution.

[0085] The leaching rate of scandium was found to be 0%.

[0086] Comparative Example 4

[0087] The same as Example 1, except that 10 parts of red mud and 8 parts of ferric sulfate were weighed (ie, the mass ratio was 1:0.8).

[0088] According to the test, the leaching rate of scandium is 58%.

[0089] Comparative Example 5

[0090] Same as Example 1, except that the calcination temperature is 650°C.

[0091] The leaching rate of scandium was found to be 52.6%.

[0092] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching, characterized in that: The following steps are involved: The red mud and ferric sulfate are mixed and ground to obtain a mixture, the mixture is roasted, water is added to the obtained roasted clinker to carry out a water leaching reaction, and the solid-liquid separation is carried out to obtain a scandium-containing leaching solution.

2. The method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching according to claim 1, characterized in that: The mass ratio of the red mud to ferric sulfate is 1.0:(1.0-1.2).

3. The method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching according to claim 1, characterized in that: The mass ratio of the red mud to ferric sulfate is 1.0:1.

2.

4. The method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching according to claim 1, characterized in that: The grinding is performed until the obtained powder passes through a 200-mesh sieve.

5. The method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching according to claim 1, characterized in that: The calcination temperature is 700° C. and the calcination time is 15 minutes.

6. The method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching according to claim 1, characterized in that: The usage ratio of the roasted clinker to water is 1g:10mL.

7. The method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching according to claim 1, characterized in that: The temperature of the water immersion reaction is 25-80° C. and the time is 30-180 minutes.

8. The method for selectively extracting scandium from red mud by ferric sulfate roasting and water leaching according to claim 1, characterized in that: The temperature of the water immersion reaction is 40° C. and the time is 30 minutes.

Citation Information

Patent Citations

  • Method for selectively leaching scandium and sodium from bayer red mud

    CN106086436A

  • Method for recycling scandium and sodium sulfate from bayer process red mud

    CN110331289A

  • Method for comprehensively recovering valuable components in red mud

    CN112795784A